Acquired alpha thalassaemia in myelodysplastic syndrome - Cheong, P (2018)
Alpha thalassaemia occurs when there is reduced production of the alpha globin compared to beta globin chains of haemoglobin. Although this almost always results from inherited defects in the alpha globin genes, over the past 50 years, a rare acquired form of alpha thalassaemia (AT) has been reported in patients with myelodysplastic syndrome (MDS); the so-called ATMDS syndrome. With one exception, in these individuals there appear to be no mutations in the alpha globin genes or their regulatory elements. However, the myeloid cells in patients with ATMDS frequently harbor mutations in the chromatin remodeling factor ATRX: an X-encoded trans-acting factor known to regulate alpha globin expression. Defining how trans-acting mutations down regulate the well characterized alpha globin genes in patients with ATMDS should increase our general understanding of how epigenetic modifiers may regulate mammalian gene expression in health and disease. The first part of this project extended our analysis of the spectrum of mutations in patients with ATMDS. In addition to the expected mutations in ATRX we also found frequent mutations in other epigenetic modifiers particularly ASXL1, U2AF1 and PHF6. The recurrent observation of mutations in all four of these genes suggested that they represent a mutational signature of ATMDS and indeed one case was retrospectively diagnosed based of this signature. Single cell analysis demonstrated that mutations in all these four genes were present within the single CD34+ stem/progenitor cells. CD34+ stem/progenitor cells from three newly identified individuals with ATMDS were expanded and differentiated along the erythroid pathway. In ATMDS most CD34+ cells did not show erythroid potential, measured by expression of the erythroid cell surface markers CD71 and CD235a. This reflects the well known block in differentiation seen in patients with myelodysplasia. Of the cells that did express erythroid markers, the ratio of alpha to non-alpha globin gene expression was reduced by 50% recapitulating, to some degree, the alpha thalassaemia observed in the peripheral blood of patients with ATMDS. Chromatin accessibility in differentiating erythroid cells, assayed by ATAC-seq, showed a generalised reduction in accessibility at the alpha globin locus. Constitutive ATRX mutations lead to mild alpha thalassaemia in ATR-X syndrome. By contrast alpha globin expression in some patients with ATMDS may be almost completely silenced with alpha/beta globin RNA and protein synthesis ratios < 0.1. This cannot be explained by ATRX mutation alone. To analyse the role of the newly identified epigenetic modifiers mutated in ATMDS, we developed a CRISPR/Cas9 editing protocol, combined with single cell FACS sorting, to model ATMDS in the human umbilical cord blood derived erythroid cell line (HUDEP-2). ATRX, PHF6, ASXL1 and U2AF1 mutations were sequentially introduced into cells derived from a single clone of HUDEP-2. This clone with the ATRX long isoform knocked out did not show any significant decrease in alpha globin gene expression. However when all four mutations had been introduced sequentially into the same clone there was a both a block in erythroid differentiation, and alpha globin gene expression was decreased. However, this was also accompanied by reduction in beta globin expression, at the same time, expression of gamma globin was strongly increased. Therefore HUDEP-2 cells do not fully recapitulate the ATMDS phenotype and this may be an indication of their limitations as a model system, nevertheless they may provide an opportunity to study the effect of mutations that affect erythroid differentiation. It seems likely that the combination of mutations in the epigenetic modifiers ATRX, ASXL1, PHF6 and U2AF1 discovered here combine to produce a severe reduction in alpha globin expression, and a more faithful cell model of this disease will be required to investigate this further.